2005
DOI: 10.1128/jcm.43.1.89-94.2005
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivities and Specificities of Spoligotyping and Mycobacterial Interspersed Repetitive Unit-Variable-Number Tandem Repeat Typing Methods for Studying Molecular Epidemiology of Tuberculosis

Abstract: The development of PCR-based genotyping modalities (spoligotyping and mycobacterial interspersed repetitive unit-variable-number tandem repeat [MIRU-VNTR] typing) offers promise for real-time molecular epidemiological studies of tuberculosis (TB). However, the utility of these methods depends on their capacity to appropriately classify isolates. To determine the operating parameters of spoligotyping and MIRU-VNTR typing, we have compared results generated by these newer tests to the standard typing method, IS6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 27 publications
2
39
2
1
Order By: Relevance
“…Thus it is very likely that the high level of transmission of this genotype may have contributed to its predominance. Although most of the clustered cases were epidemiologically supported, one should not dismiss the possibility that some patients may not be part of a recent transmission chain, since, as previously shown, the Spol-MIRU12 combination used in this study could lead to misclassification (Scott et al, 2005). By contrast, the ST42 genotype displayed low clustering, was more widespread than ST50, and was found to be predominant in the sample from 1990, accounting for 35.4 % (11 out of 31) of TB cases.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it is very likely that the high level of transmission of this genotype may have contributed to its predominance. Although most of the clustered cases were epidemiologically supported, one should not dismiss the possibility that some patients may not be part of a recent transmission chain, since, as previously shown, the Spol-MIRU12 combination used in this study could lead to misclassification (Scott et al, 2005). By contrast, the ST42 genotype displayed low clustering, was more widespread than ST50, and was found to be predominant in the sample from 1990, accounting for 35.4 % (11 out of 31) of TB cases.…”
Section: Discussionmentioning
confidence: 99%
“…Second, 20 (87.0%) of 23 MDR TB isolates were strains that matched by 3 different molecular subtyping methods. It is possible that 2 additional isolates (22 total) were part of the outbreak as well because they matched the outbreak strain according to spoligotyping and RFLP results and differed by only 1 locus according to MIRU; therefore, this difference may represent a change in genotype in the same clone over time (26). Third, elevated rates of tuberculin reactivity in household contacts of smear-positive patients suggest substantial recent transmission, not simply endemic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a generally lower rate of change of these 12-locus patterns than that of IS6110-RFLP (15,18,25), secondary IS6110 fingerprinting of the isolates clustered by this combined strategy is nevertheless necessary to reach the maximal resolution needed in some situations (4,18). However, another investigation suggested that this MIRU-VNTR typing combined with spoligotyping was inadequate for population-based studies because it provided a too-low resolution power and, more surprisingly, because MIRU-VNTR genotypes were apparently too frequently unstable among presumably related isolates (19). However, these parameters were determined by taking clustering defined by IS6110-RFLP as a sole reference, in the absence of any contact tracing data.…”
mentioning
confidence: 99%
“…However, these parameters were determined by taking clustering defined by IS6110-RFLP as a sole reference, in the absence of any contact tracing data. Since it is known that IS6110-RFLP does not per se unambiguously define all related or unrelated isolates (see, for example, references 29, 32, and 34), unequivocal interpretation of all of the divergences between the typing methods in that study (19) was not possible. In a recent study based on an worldwide collection of tubercle bacillus isolates (24), we defined an optimized set of 24 MIRU-VNTR loci, including a subset of 15 discriminatory loci proposed to be used as a first-line typing method.…”
mentioning
confidence: 99%